Broken Insulator Effects on Charge Distribution Measurement along Suspension Insulators - Rosli, H.; Othman, N. A.; M. Piah, M. A.; M. Jamail, N. A.; M. Yousof, M. F.; Ismail, M. N. (International Journal of Integrated Engineering, 2020)
In the early years of power system network, porcelain and glass were used and still continuously serve the overhead lines to the present time. Obviously, they can provide distinction services over a long period of time. In spite of that, one or two of the insulators in the suspension may be damaged due to some cases yet the suspension insulator is believed can still be used for a certain amount of time. By studying some research from previous works, it is accepted that the different properties of porcelain and glass type had made these insulators vary in their respective capabilities to serve overhead lines. This paper endeavours the distribution of charge for the porcelain suspension insulator using chamber method. Finite element software particularly QuickfieldTM was used in simulation purpose to validate the experimental results. Similar patterns of charge distributions were acquired for both experimental and simulation works.